2020
DOI: 10.3390/jcm9103117
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Shock Clinical Presentation, Management, and In-Hospital Outcomes in Patients Admitted to the Acute Cardiac Care Unit of a Tertiary Hospital: Does Gender Play a Role?

Abstract: Cardiogenic shock (CS), as the most severe form of heart failure, is associated with very high mortality rates despite therapeutic advances in the last decades. Gender differences in outcomes have been widely reported regarding several cardiovascular diseases. The aim of our study was to evaluate potential gender disparities in clinical presentation, management, and in-hospital outcomes of all (n = 138) patients admitted to the Acute Cardiac Care Unit of a tertiary hospital from 2013 to 2019. Information on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…In our current study, we found CS to have poor outcome [13][14] .AMI is the mainreason of bereavement in the recentera. CS most frequentlytranspires as animpediment of AMI 15 . Patients with CS have a higher risk of death and cardiovascular complications during AMI 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we found CS to have poor outcome [13][14] .AMI is the mainreason of bereavement in the recentera. CS most frequentlytranspires as animpediment of AMI 15 . Patients with CS have a higher risk of death and cardiovascular complications during AMI 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Although in-hospital mortality is higher amongst Hispanics (74%) and African Americans (65%), these differences disappear when controlled for access to primary PCI ( 20 ). Similarly, the higher mortality observed amongst women with AMI-CS ( 21 ), is reduced with the use of standardized management algorithms ( 22 ).…”
Section: Current Landscapementioning
confidence: 99%
“…Išsivysčius kardiogeniniam šokui, mirštamumas siekia iki 50 proc. [2]. Mokslinės literatūros duomenimis, minėtų kritinių būklių metu sėkmingai naudojamos įvairios pagalbinės kraujotakos priemonės, lemiančios iki 70 proc.…”
Section: įVadasunclassified